2018
DOI: 10.2174/1570159x15666171017111532
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Alterations Across Eating Disorders: A Narrative Review of fMRI Studies

Abstract: Findings on reward processing in both AN and BN patients point to the presence of altered sensitivity to salient food stimuli in striatal regions and to the possibility of hypothalamic inputs being overridden by top-down emotional-cognitive control regions. Additionally, innovative new lines of research suggest that increased activations in fronto-striatal circuits are strongly associated with the maintenance of restrictive eating habits in AN patients. Although significantly fewer studies have been carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 139 publications
(170 reference statements)
5
90
0
1
Order By: Relevance
“…These changes in the dorsal striatum subsequently consolidate the compulsive nature of the addiction over time. The ventral tegmental area and nucleus accumbens are also highly involved in the processing of taste reward and, as cited above, reduced dopamine binding in these same regions of the striatum has been noted in BN as well as obesity (as is also seen in individuals with drug addictions) …”
Section: The Concept Of Food Addictionmentioning
confidence: 77%
“…These changes in the dorsal striatum subsequently consolidate the compulsive nature of the addiction over time. The ventral tegmental area and nucleus accumbens are also highly involved in the processing of taste reward and, as cited above, reduced dopamine binding in these same regions of the striatum has been noted in BN as well as obesity (as is also seen in individuals with drug addictions) …”
Section: The Concept Of Food Addictionmentioning
confidence: 77%
“…Evidence suggests that individuals with AN-R and AN binge eating/purging subtype (AN-BP) may demonstrate different patterns in reward responding (Fassino et al, 2002). In order to reduce noise within a limited clinical sample, we selected to examine AN-R as representative of the core psychopathology on AN, since this group has been implicated as a distinct phenotype with less mechanistic overlap with other eating disorders (e.g., bulimia nervosa, binge eating disorder) compared to AN-BP (Brooks, Rask-Andersen, Benedict, & Schiöth, 2012; Steward et al, 2017). To otherwise increase the representativeness of the AN-R group, psychiatric comorbidity was permitted outside of the exclusionary disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies of individuals with AN using structural and task-based functional imaging have found evidence of abnormalities in brain regions associated with reward, such as the NAcc and orbito-frontal cortex (OFC) (Brooks et al, 2011; Frank, Shott, Hagman, & Mittal, 2013; Holsen et al, 2012; Steward et al, 2017), as well as those associated with habit (Bailer et al, 2017; Foerde et al, 2015; Rothemund et al, 2011; Titova, Hjorth, Schiöth, & Brooks, 2013) including the dorsal striatum and dorsolateral prefrontal cortex (Balleine & O’Doherty, 2010). Most of the studies examining functional patterns in circuitry associated with reward and habit learning in AN have examined responses to specific cues, such as those salient to the illness (e.g., food, thin bodies) or stimuli that are typically considered rewarding (e.g., money).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that treatment success in BN, BED, and obesity might be impaired by general and, more importantly, food‐specific self‐regulatory deficits (e.g., Brockmeyer et al, ; Manasse et al, ; Sysko et al, ). A number of studies suggested that the recruitment of the prefrontal control circuitry is altered in these conditions, which might explain the diminished self‐regulatory abilities in several executive functions, such as impulsivity, set shifting, or inhibition (Lavagnino, Arnone, Cao, Soares, & Selvaraj, ; Steward, Menchón, Jiménez‐Murcia, Soriano‐Mas, & Fernández‐Aranda, ). These alterations are particularly pronounced in response to food cues and present, for example, in a decreased activation of the prefrontal cortex in individuals with BN and those with obesity and increased activation of the orbitofrontal cortex in individuals with BED as compared with healthy individuals (Friederich, Wu, Simon, & Herzog, ; Lavagnino et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Existing systematic and nonsystematic reviews investigating the relationship between brain functions, cognitive functions, and eating behaviour in BN, BED, and obesity focused on findings from neuroimaging studies using functional magnetic resonance imaging (fMRI), MRI, positron emission tomography (Carnell, Gibson, Benson, Ochner, & Geliebter, ; Kessler, Hutson, Herman, & Potenza, ; Lavagnino et al, ; Steward et al, ), or analyzed event‐related potentials (ERPs), and sleep EEG (Jáuregui‐Lobera, ; Wolz et al, ). However, these reviews did not provide information on abnormalities in the EEG power spectrum in BN, BED, and obesity, which is, however, a prerequisite for the development of EEG neurofeedback paradigms, targeting disorder‐specific abnormalities in the EEG power spectrum in these conditions.…”
Section: Introductionmentioning
confidence: 99%